1993
DOI: 10.1093/infdis/168.1.222
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Helicobacter pylori in Chile: Vegetables May Serve as One Route of Transmission

Abstract: Helicobacter pylori infection is very common in Chilean adults, but the age-related prevalence, risk factors for infection, and mode of transmission in Chilean children are unknown. An ELISA was used to test for H. pylori antibodies in 1815 Chileans < 35 years of age. Seropositivity was > 60% in lower socioeconomic groups. H. pylori seropositivity correlated with increased age, low socioeconomic status, and consumption of uncooked vegetables by use of a logistic regression analysis. Risk factors that reached m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
2
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(143 citation statements)
references
References 10 publications
9
123
2
8
Order By: Relevance
“…Alcohol consumption and smoking were also not associated with infection [16,17]; the same was true for recent antibiotic use and contact with pets [18]. Some epidemiological studies have indicated an association between the ingestion of raw vegetables and H pylori infection [19]. We found no such association, nor did Brown et al [20].…”
Section: Discussionsupporting
confidence: 42%
“…Alcohol consumption and smoking were also not associated with infection [16,17]; the same was true for recent antibiotic use and contact with pets [18]. Some epidemiological studies have indicated an association between the ingestion of raw vegetables and H pylori infection [19]. We found no such association, nor did Brown et al [20].…”
Section: Discussionsupporting
confidence: 42%
“…This could explain the wide range of habits and conditions, including cutlery sharing, bed sharing, overcrowding, consumption of raw food and presence of pets, that have been found to be associated with infection in different studies. [33][34][35][36] A recent study on the seroprevalence of infection among blood donors identified race (nonwhite), low educational level, previous endoscopy and age as risk factors for H. pylori seropositivity in a multivariate analysis. 37 Other authors have stressed that the water supply could be the source of the infection, but this variable was not tested in the present study, since all the subjects had access to the same water distribution system.…”
Section: Discussionmentioning
confidence: 99%
“…This differential susceptibility may be directly related to the long-term clinical outcome. It has been reported that the males are at a greater risk of H pylori clinical manifestations [36,37] . These observation may account for higher prevalence of duodenal ulcer and gastric cancer in males.…”
Section: Discussionmentioning
confidence: 99%